2013
DOI: 10.2134/agronj2012.0473
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Relative Corn Yield with Soil‐Nitrate Tests under Irrigated Mediterranean Conditions

Abstract: Soil nitrate tests are a useful tool to manage corn (Zea mays L.) N fertilization under rainfed conditions, but the feasibility of using these tests under irrigated Mediterranean conditions has received little attention. The objective of this study was to determine whether the preplant nitrate test (PPNT), pre-sidedress nitrate test (PSNT), and soil available-N content test (PPNT or PSNT plus N fertilizer) could accurately predict relative corn yield (RY) under irrigated, high-yielding conditions. Twentyone co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 28 publications
4
16
4
1
Order By: Relevance
“…Mid-April is the most common SD in the studied area, possibly because of the cooler temperatures during mid-March SD and the shorter growing season associated with mid-May SD. The average grain yield obtained in the study is similar to the averages reported by Cela et al [32] (13.6 ± 0.4 Mg ha −1 ) in the same area.…”
Section: Grain and Biomass Yieldssupporting
confidence: 90%
“…Mid-April is the most common SD in the studied area, possibly because of the cooler temperatures during mid-March SD and the shorter growing season associated with mid-May SD. The average grain yield obtained in the study is similar to the averages reported by Cela et al [32] (13.6 ± 0.4 Mg ha −1 ) in the same area.…”
Section: Grain and Biomass Yieldssupporting
confidence: 90%
“…As observed for the VIs, knowledge of the N available in the topsoil layer slightly increased the accuracy of the model. The GYON r and GYON a were respectively determined at 216.8 and 248.6 kg N ha −1 , similar to the N rates reported in previous studies in the area [8,67,69,70]. However, the maize N extractions were probably not completely covered by the determined GYON r and GYON a in the linear-plateau model.…”
Section: Grain Yield and Economic Return Responses To N Rates And Avasupporting
confidence: 84%
“…Subsequent papers directly calculated a critical concentration of soil nitrate from the relationship of relative yield with soil nitrate concentrations (Blackmer et al, 1989;Fox et al, 1989;Cela et al, 2013).…”
Section: Pre-sidedress Nitrate Testmentioning
confidence: 99%